Peran Wakaf dalam Perluasan Aset Pendidikan dan Pemberdayaan Ekonomi Umat di Wilayah Kecamatan Kasemen Kota Serang Provinsi Banten (Studi di Badan Wakaf Indonesia Kota Serang Provinsi Banten) - Ikhsan Ikhsanuddin; Syafuri Bai; Masykuroh Nihayatul (TSARWAH, 2022)
This study aims to determine the role and the strategies of Waqf in the Expansion of Educational Assets and Moslems' Economic Empowerment in the Kasemen District, Serang City, Banten Province at The Al-Khairiyah Badamusalam Islamic Education Foundation in Serang City. This research is field research with a shar'i and socio-historical approach that used triangulation techniques (combined) in the collection of its data in the form of key informants, and the instruments used are interviews and observation. Data is collected by collecting it in the field and through archived important documents. The data analysis technique used is descriptive analysis. The results of this research revealed that the role of Waqf in the Expansion of Educational Assets and Moslems Economic Empowerment in the Kasemen District, Serang City, Banten Province guided by the concept of Islamic management which departs from five basic principles, namely (a) trust (b) intelligence (c) transparency (d) honesty, and (e) protection. In managing the Waqf assets, the Foundation distributes the financial support that was sourced from education fees and donations that are allocated to fund high-quality educational facilities. The strategies of Waqf development, are:1) Implementing the partnership program with third parties, whether linked to the institution or to the skills of students. 2) Implementation of skills training according to the experiences of each of the students. In managing and developing the Waqf assets.